Highly Active and Robust Cp* Iridium Complexes for Catalytic Water Oxidation - Hull, Jonathan F. (2009)
[Image: see text] A series of Cp*Ir catalysts are the most active known by over an order of magnitude for water oxidation with Ce(IV). DFT calculations support a Cp*Ir=O complex as active species.